Stitching Generations Together: The Isadore and Mary Rose Charlo Family Exhibit and Doll Sewing Workshops ... : Tłı̨chǫ Cultural Commons Research Series, Volume 2 ... - Bourgeois, Rebecca L.; Gelderman, Karen; Goldberg, Elizabeth Libby (University of Alberta Library, 2023)
This booklet is the second volume of the Tłı̨chǫ Cultural Commons Research Series which is centered around the work being done surrounding the development of the Tłı̨chǫ archive and museum. Here we detail the first installation of the rotating Tłı̨chǫ Family Exhibit, curated by Elizabeth Sanspariel to tell the story of her parents Isadore and Mary Rose Charlo. The exhibit and doll-sewing event originated from discussions at the Night at the Museum archival sharing circle (see Tłı̨chǫ Cultural Commons Research Series vol. 1) that took place in December 2022. Both at this event and in interviews that followed, we heard that community members would like to see their family members and teachers honoured in the museum, rather than just the chiefs or political leadership. Thanks to the donation of a new glass display case by the Prince of Wales Northern Heritage Centre, this feedback was able to be incorporated into the museum. Tłı̨chǫ Arts and Heritage Facilitator Karen Gelderman knew that many Tłı̨chǫ families ...